Posing Frege’s Puzzle Without Presupposing Linguistic Senses - Bochner, Gregory (2015)
In her challenging paper “Can Frege Pose Frege’s Puzzle?”, Stavroula Glezakos argues that Frege’s presentation of his famous puzzle is circular: the puzzle is supposed to establish the need for Senses, and yet, she contends, in order to generate the puzzle, Frege should already need to invoke Senses. In response I argue that the puzzle should be posed without essentially relying on language and words. I try to show that the real puzzle is not about identity sentences, but about the cognitive value of concepts and thoughts, and also that, in order to pose the puzzle, it is necessary to presuppose, not Senses, but certain transparency principles for concepts and thoughts.